ESTABLISHING INTERDISCIPLINARY CONNECTIONS BY SOLVING PHYSICAL PROBLEMS OF A MILITARY-PRACTICAL NATURE (Web of Teachers: Inderscience Research, 2025)
The article examines the importance of theoretical and methodological study of the processes of unification of disciplines in the field of pedagogy and their application in practice based on the analysis of scientific research conducted by world scientists in this field, from the point of view of the need to provide a modern education system with the organization of training based on interdisciplinary connections. Today it has been established that the study of physics in higher military educational institutions in didactic interaction with special military educational disciplines, as a result of solving existing problems, contributes to increasing the effectiveness of officer training. In particular, it is shown that the solution to the problem of solving physics problems in the context of interdisciplinarity, the experience accumulated in the educational systems of schools and civilian universities on this problem serve as the basis for improving the organization of the educational process in higher military educational institutions.